Trade in the small- and micro-entreprise sector in Kenya and other countries in Eastern and Southern Africa - Poul Ove Pedersen (Danish Institute for International Studies (DIIS), 2005)
Since the famous ILO report on the informal sector in Kenya was published in 1972 the smallscale enterprises have been recognised to play an important role in the Kenyan economy as in other African countries. However, although often more than half of all the small enterprises are traders. Most small enterprise policies have focussed almost entirely on the small scale producers. The small-scale traders have generally been seen as unproductive activities with no positive role to play in development, a sign of poverty, although they are responsible for a large share of the national distribution system. The paper attempts to look at this paradox and investigate the role of the small scale traders in the small enterprise sector and in the development process.
Keywords: 330; KMU; Einzelhandel; Unternehmensnetzwerk; Ostafrika; Südafrika; Kenia